2018
DOI: 10.18632/oncotarget.25417
|View full text |Cite
|
Sign up to set email alerts
|

Anion exchanger 2 suppresses cellular movement and has prognostic significance in esophageal squamous cell carcinoma

Abstract: BackgroundRecent studies have reported essential roles for various intracellular pH regulators in epithelial carcinogenesis and tumor progression. The aims of the present study were to investigate the role of anion exchanger 2 (AE2) in the regulation of tumor progression-related genes and the prognostic value of its expression in esophageal squamous cell carcinoma (ESCC).ResultsAE2 was strongly expressed in KYSE170 and TE13 cells. The depletion of AE2 in these cells increased cell migration and inhibited the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
(46 reference statements)
0
13
0
Order By: Relevance
“…Recent studies indicated that reductions in anion exchanger 2 (AE2) could activate MMP signaling pathways and enhance cellular movement in ESCC. Further analysis showed that AE2 was crucial to the poor prognosis of patients with ESCC [ 43 ]. Subsequently, Han et al found that MMP12 was closely related to nodal metastasis, tumor grade and staged poor survival of ESCC owing to its high expression in tumor cells [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicated that reductions in anion exchanger 2 (AE2) could activate MMP signaling pathways and enhance cellular movement in ESCC. Further analysis showed that AE2 was crucial to the poor prognosis of patients with ESCC [ 43 ]. Subsequently, Han et al found that MMP12 was closely related to nodal metastasis, tumor grade and staged poor survival of ESCC owing to its high expression in tumor cells [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bodily and cellular functions are controlled by various factors including ions such as Na + , K + , Ca 2+ , Mg 2+ , Zn 2+ , and Cl − [ 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. On the one hand, pH (−log[H + ]) is recognized as one of classical items considered to be already fully understood in roles and mechanisms of homeostasis.…”
Section: Variety Of the Interstitial Fluid Phmentioning
confidence: 99%
“…Celay et al addressed the role of AE2 and its target peptide reduced tumor growth in vivo [30]. Enhanced AE2 promotes ovarian cancer progression by activating mTOR signaling [17]; whereas, reduction of AE2 enhances cellular migration via the activation of MMP pathways in the esophageal squamous cell carcinoma [31]. Despite the controversial effect of AE2 on tumorigenesis, as a drug repurposing, the attenuation of AE2 and its supportive enzyme CA12, and the inhibitory effect on cell migration by DSF in lung and breast cancer cells, provides evidence supporting the therapeutic potential of DSF against cancer as well as alcoholism.…”
Section: Discussionmentioning
confidence: 99%